Conceptual risk assessment for new township infrastructure expansion at Kuantan - Mohammad Affendy, Omardin; M. F., Ishak; N. F., Omar; K. J., Abd Hamid; F. Z., Mansur; Lau, P. D.; N. A., Tutur; M., Mustafa; K., Mansor; Teo, M. Y.; Lee, J. X. (Penerbit Universiti Malaysia Pahang, 2023)
This paper intends to contribute about the risk assessment on New Township located at Kuantan. Researchers found that, it has a lot of risk that will occur at that area. Researchers found that it have 5 possible risk like disease, flooding, traffic risk, soil erosion and the improper drainage system. Then, researchers will choose the top 3 major risk to do the risk assessment. So, researchers choose traffic risk, soil erosion and the improper drainage system as our major risk in this project. Lastly, researchers also have implement the solution to solve the risk.